A clinical case of co-occurring mental disorder and coronavirus infection - M. B. Jumagaliyeva; D. N. Ayaganov; V. L. Yuldashev; L. R. Akhmadeeva (Бюллетень сибирской медицины, 2023)
(COVID-19). In addition to systemic and respiratory symptoms, SARS-CoV-2 causes neurological disorders, as it is a neurotropic virus. Many scientists assume that SARS-CoV-2 can enter the nervous system through the functional receptor of angiotensin-converting enzyme 2, which is present in glial cells, neurons, skeletal muscles, and other organs. Neurological complications are manifested by damage to the central nervous system, peripheral nervous system, and cranial nerves, as well as by mental disorders. Mental illnesses develop due to neuroinflammation and neuronal death after brain infection with SARS-CoV-2.The article describes a clinical case of a 63-year-old man with the co-occurring novel coronavirus infection and obvious mental disorder who has never had any mental illnesses before. The given clinical example demonstrates the importance of studying the cause-and-effect relationship between COVID-19 and mental illness. In the mediumand long-term perspective, COVID-19 is expected to result in mental health disorders during COVID-19 recovery. Besides, an increase in the number of patients with mental disorders who were mentally healthy before COVID-19 infection is also expected.